Seismic Performance of Partially Dismantled Buildings - Shrestha, Jagat Kumar (Journal of the Institute of Engineering, 2018)
This study carries out the comparative study of Seismic Performance of residential buildings after partial dismantling for road widening works in Kathmandu city. Two types of buildings were taken for the study, i.e. 4 storey building and 6 storey building. The Buildings were assessed for bare frames. The detail level of the seismic evaluation was carried out by preparing 3-D modeling of the buildings in SAP2000 software by nonlinear static pushover analysis. The capacity of the buildings has been found significantly decreased after the partial dismantling of the building due to the road widening works. The behavior of buildings has been found like a strong beam and weak column mechanism. Journal of the Institute of Engineering, 2017, 13(1): 69-77